Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Hasil Belajar Matematika Peserta Didik Kelas III SDN 5 Rasau Jaya - Fitriana Fitriana (CV. Ulil Albab Corp, 2023)
The Effect Of The Make A Match Type Cooperative Learning Model On The Mathematics Learning Outcomes Of Grade III Students At SDN 5 Rasau Jaya. Outcomes this study aims to determine the effect of the make a match learning model on the mathematics learning outcomes of class III students at SDN 5 Rasau Jaya. The research method used is an experimental method with the form of research used is a pre-experimental design. The experimental design carried out in this study used the one-group pretest-posttest design. The independent variable (X) is the make a match cooperative learning model, while the dependent variable (Y) is the learning outcome. The population included in this study were students in class III A and III B. Class III A consisted of 12 boys and 9 girls. While class III B consisted of 14 girls and 8 boys. The sample in this study were class III A students at SDN 5 Rasau Jaya. The techique used for data collection is a test.